Acute phase treatment of venous thromboembolism: advanced therapy - Konstantinides, Stavros V.; Wärntges, Simone (Thrombosis and Haemostasis, 2015)
Venous thromboembolism, which encompasses deep-vein thrombosis and acute pulmonary embolism (PE), represents a major contributor to global disease burden worldwide. For patients who present with cardiogenic shock or persistent hypotension (acute high-risk PE), there is consensus that immediate reperfusion treatment applying systemic fibrinolysis or, in the case of a high bleeding risk, surgical or catheterdirected techniques, is indicated. On the other hand, for the large, heterogeneous group of patients presenting without overt haemodynamic instability, the indications for advanced therapy are less clear. The recently updated guidelines of the European Society of Cardiology emphasise the importance of clinical prediction rules in combination with imaging procedures (assessment of right ventricular function) and laboratory biomarkers (indicative of myocardial stress or injury) for distinguishing between an intermediate and a low risk for an adverse early outcome. In intermediate-high-risk PE defined by the presence of both right ventricular dysfunction on echocardiography (or computed tomography) and a positive troponin (or natriuretic peptide) test, the bleeding risks of full-dose fibrinolytic treatment have been shown to outweigh its potential clinical benefits unless clinical signs of haemodynamic decompensation appear (rescue fibrinolysis). Recently published trials suggest that catheter-directed, ultrasoundassisted, low-dose local fibrinolysis may provide an effective and particularly safe treatment option for some of these patients.
Keywords: Pulmonary embolism; risk-adjusted treatment; fibrinolysis; catheter-directed treatment; pharmacomechanical therapy